Estimating and scheduling the water needs of the alfalfa crop using Cropwat 8.0 model in the Kaam Agricultural Project – Libya (Libya Journal of Geographical Studies, 2025)
The study aims to identify the amounts of water needed to irrigate the Alfalfa crop as well as the amounts of evaporation according to the current climate of the kamam agricultural project area and based on the standards of the food and Agriculture Organization (FAO). it also aims to develop an irrigation calendar that project farmers can follow and raise their awareness of the proper routine of irrigation during dry periods based on the Cropwat 8.0 model, which are irrigation methods based on scientific foundations of water-saving irrigation technology, the study used the analytical and descriptive approach, and reached several results, the most important of which is that the Alfalfa crop in the Kaam Valley agricultural project requires irrigation a total of 1850.5 mm and a net irrigation of 1555.5 MM, through 22 irrigations during the season, and that the needs of the hectare The project has a capacity of 18,505 cubic meters per season, and it is important to conduct studies and research using the crop watt model for all crops in the project area so that we can improve the management of Water Resources in the region as well as improve production.
Keywords: Kaam project; scheduling water requirements for alfalfa; crop water requirements; field capacity; Watering intervals